Residual Compressive Strength Prediction Model for Concrete Subject to High Temperatures Using Ultrasonic Pulse Velocity - Kim, Wonchang; Choi, Hyeonggil; Lee, Taegyu (Materials, 2023)
This study measured and analyzed the mechanical properties of normal aggregate concrete (NC) and lightweight aggregate concrete (LC) subjected to high temperatures. The target temperature was set to 100, 200, 300, 500, and 700 °C, and W/C was set to 0.41, 0.33 and 0.28 to evaluate high temperature properties at various intensities. Measurement parameters included mass loss, compressive strength, ultrasonic pulse velocity (UPV), and elastic modulus. We compared the residual mechanical properties between the target and preheating temperatures (20 °C) and then analyzed the correlation between UPV and compressive strength. According to the research findings, after exposure to high temperatures, LC demonstrated a higher mass reduction rate than NC at all levels and exhibited higher residual mechanical properties. The results of analyzing the correlation between compressive strength and UPV for concrete subjected high temperatures were very different from the compressive strength prediction equation previous proposed at room temperature, and the error range of the residual strength prediction equation considering W/C was reduced.